PEMANFAATAN APLIKASI SISTEM NASKAH DINAS ELEKTRONIK (SINDE) DI LEMBAGA LAYANAN PENDIDIKAN TINGGI WILAYAH XVI - Endang Hamzah; Ellys Rahman; Yahya Antu (Smart Education, 2026)
Abstract: This type of research is a Descriptive Research Type, with a qualitative approach. The purpose of this research is to obtain a clear picture of the use of the Electronic Service Script System (SINDE) application in the Region XVI Higher Education Service Institution by using a focus such as Understanding, Infrastructure and Leadership Support. Based on the results of the research reviewed from the understanding, in this case the level of understanding of some employees is still diverse in understanding the use of the Electronic Service Manuscript System (SINDE) application at the Region XVI Higher Education Service Institution. Some employees do not understand and still need help from colleagues who know better, even some of them learn on their own without the help of others. This condition shows that official training support from agencies is still lacking. As a result, the user's understanding depends on their individual personal initiative, which will obviously affect the level of effectiveness and consistency in the use of the application in the work environment. In terms of infrastructure, there are still several technical obstacles, such as errors during login, dependence on internet connections, and server interruptions. This indicates that the system is not yet fully stable, so it needs to be improved in terms of its stability and reliability. Then in terms of leadership support for the use of the Electronic Service Manuscript System application, it is very positive and strategic in encouraging digital transformation in the field of newspaper administration. However, in practice, there is still a parallel use between digital systems and manual processes, which indicates that support from leaders needs to be accompanied by strengthening a digital work culture and continuous training for employees. Through this research, it is hoped that effective solutions can be found to increase the use of the Electronic Service Script System Application (SINDE) at the Region XVI Higher Education Service Institution, as well as providing recommendations for the development of a better management information system in the future. Keywords: Utilization, Electronic Service Manuscript System, LLDIKTI. Abstrak: Jenis penelitian ini adalah Penelitian Deskriptif, dengan pendekatan kualitatif. Tujuan penelitian ini adalah untuk mendapatkan gambaran yang jelas tentang penggunaan aplikasi Sistem Layanan Elektronik (SINDE) di Institusi Layanan Pendidikan Tinggi Wilayah XVI dengan menggunakan fokus seperti Pemahaman, Infrastruktur, dan Dukungan Kepemimpinan. Berdasarkan hasil penelitian yang ditinjau dari pemahaman, dalam hal ini tingkat pemahaman sebagian karyawan masih beragam dalam memahami penggunaan aplikasi Sistem Manuskrip Layanan Elektronik (SINDE) di Lembaga Pelayanan Pendidikan Tinggi Wilayah XVI. Sebagian karyawan belum memahami dan masih membutuhkan bantuan dari rekan yang lebih berpengalaman, bahkan sebagian belajar sendiri tanpa bantuan orang lain. Kondisi ini menunjukkan bahwa dukungan pelatihan resmi dari instansi masih kurang. Akibatnya, pemahaman pengguna bergantung pada inisiatif pribadi masing-masing, yang tentunya akan memengaruhi tingkat efektivitas dan konsistensi penggunaan aplikasi di lingkungan kerja. Dari segi infrastruktur, masih terdapat beberapa kendala teknis, seperti kesalahan saat login, ketergantungan pada koneksi internet, dan gangguan server. Hal ini menunjukkan bahwa sistem belum sepenuhnya stabil, sehingga perlu ditingkatkan dari segi stabilitas dan keandalannya. Kemudian dari segi dukungan kepemimpinan untuk penggunaan aplikasi Sistem Manuskrip Layanan Elektronik, sangat positif dan strategis dalam mendorong transformasi digital di bidang administrasi surat kabar. Namun, dalam praktiknya, masih terdapat penggunaan paralel antara sistem digital dan proses manual, yang menunjukkan bahwa dukungan dari para pemimpin perlu disertai dengan penguatan budaya kerja digital dan pelatihan berkelanjutan bagi karyawan. Melalui penelitian ini, diharapkan dapat ditemukan solusi efektif untuk meningkatkan penggunaan Aplikasi Sistem Skrip Layanan Elektronik (SINDE) di Lembaga Pelayanan Perguruan Tinggi Wilayah XVI, serta memberikan rekomendasi untuk pengembangan sistem informasi manajemen yang lebih baik. di masa depan. Kata kunci: Pemanfaatan, Sistem Manuskrip Layanan Elektronik, LLDIKTI.